Foreign policy challenges in the 21st century - Heazle, Michael; Griffiths, Martin 1961-; Conley, Tom 1966- (Edward Elgar, 2009)
This book explores the emerging challenges to foreign policymaking in liberal democracies and the adequacy of the marketplace of ideas in responding to these challenges. Looking at foreign policy challenges as diverse as democratization, globalization and climate change, from the role of values in environmental debate to the Iraq invasion and the war on drugs, the contributors critically examine how key global issues are framed in public debate across three of the worlds most mature liberal democracies: the US, the UK, and Australia. The book contributes to a better understanding of the limits of the marketplace of ideas in helping to produce wise and accountable policy, and how those limits may soon be overcome.Examining how key global issues are framed in foreign policy debate across a range of liberal democratic societies, this book will strongly appeal to academics and students with an interest in international relations, policymaking and politics, as well as to governmental and think tank policymakers and advisors.